DSGE forecasts of the lost recovery - Michael Cai; Marco Del Negro; Marc P. Giannoni; Abhi Gupta; Pearl Li; Erica Moszkowski (Federal Reserve Bank of New York, 2018)
The years following the Great Recession were challenging for forecasters. Unlike other deep downturns, this recession was not followed by a swift recovery, but generated a sizable and persistent output gap that was not accompanied by deflation as a traditional Phillips curve relationship would have predicted. Moreover, the zero lower bound and unconventional monetary policy generated a policy environment without precedents. We document the real real-time forecasting performance of the New York Fed dynamic stochastic general equilibrium (DSGE) model during this period and explain the results using the pseudo real-time forecasting performance results from a battery of DSGE models. We find the New York Fed DSGE model's forecasting accuracy to be comparable to that of private forecasters - and notably better, for output growth, than the median forecasts from the FOMC's Summary of Economic Projections. The model's financial frictions were key in obtaining these results, as they implied a slow recovery following the financial crisis.
Keywords: C11; C32; C54; E43; E44; 330; DSGE models; real-time forecasts; Great Recession; financial frictions